Pengembangan Keterampilan Ecoprint untuk Pemberdayaan Ibu PKK di Kembangsari Berbasis Ekonomi Kreatif - Shofwatunnida Septarini; Mutia Perwita Sari; Vitro Rahmat; Arif Rahman Hakim (Jurnal Teknologi Informasi untuk Masyarakat, 2026)
This community service program aims to enhance the skills, creativity, and economic potential of women members of the PKK group in Kembangsari Village through a training session on leaf-based ecoprint techniques using cotton fabric. The activity was conducted in a single mentoring session involving 30 participants. The implementation method consisted of delivering fundamental material on ecoprint principles, demonstrating the pounding technique, facilitating hands-on practice, and evaluating both the participants’ artworks and their attitudinal changes before and after the training. Throughout the activity, participants were able to understand each production stage ranging from leaf selection, motif arrangement, and pounding, to the color-fixation process. The resulting ecoprint works showed good visual quality, although several participants required additional time to determine more harmonious motif compositions. In terms of affective outcomes, there was a noticeable increase in motivation and self-confidence: 20 participants expressed their intention to continue practicing ecoprint at home, and 12 participants identified ecoprint as a potential source of additional income. Challenges encountered during the program included inconsistent leaf pigment quality, variations in leaf conditions, and limited time that prevented exploration of other ecoprint techniques such as bundling and tataki-zome. However, these challenges were relatively minor and provided opportunities for further capacity-building activities. Overall, this program successfully improved participants’ knowledge and practical skills, while also pening prospects for the establishment of an ecoprint craft group as a creative local product identity of Kembangsari.